A call to the intellectual as a collective subject - Marín Escobar, Paloma (Revista Colombiana de Ciencias Sociales, 2026)
The intellectual is often imagined as a solitary wanderer—someone confined all day in a study, backed by a sturdy wooden library, an ashtray to the left, a cup of coffee to the right, and, in the distance, a window where the sunset appears and, at night, the cicadas sing. Indeed, when Plato, seeking to problematize the origin of intellectual ingenuity, the root of knowledge, and the enigma of wisdom, writes the myth of the cicadas in his Phaedrus, he seems to be thinking of a subject who must withdraw from the world to find inspiration in the hidden voice of nature. This subject forgets to attend to basic needs or daily concerns, for their soul is cast toward ideas, and their ultimate purpose is to compose the truest discourses—to encode, in the form of language, what the cicadas sing to them. This idea, which no doubt serves to explain the faculty that drives us to create knowledge, to name the things of the world with virtue, truth, and goodness, ought, however, to be expanded—beyond the individual who walks alone along the frontiers of reason— to consider the subject of knowledge as a being in community, as a collective subject.